Konsepsi Zakat Untuk Papan Perspektif Fukaha Kontemporer - Waluya, Atep Hendang; Sofyan, Syaakir; Matondang, M. Reza Prima; Mulauddin, Aforisma (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2024)
Islam views that clothing, food and shelter are ḍarūriyyat matters in order to safeguard the human soul. This study aims to analyze the various opinions of contemporary scholars about the utilization of zakat for housing for the poor. The method used in this research is a qualitative method with a literature study pattern. The results of this study indicate that the jurists agree that zakat may be distributed for the needs of the poor because it includes their basic needs, but in terms of the mechanism they have different opinions and are divided into two opinions. First, zakat may be utilized to rent houses for the poor, but may not build or buy houses for them. Second, zakat may be used to build, buy or rent houses for the poor. The reason for the first group not allowing zakat funds to build houses for the poor is because the construction of houses requires large funds, and can result in other poor people not receiving zakat funds and may not give zakat funds for more than one year's needs for the poor. As for those who allow zakat funds to be used to build houses or buy houses for the poor, they reason that there is no argument forbidding or ordering it and may provide zakat funds continuously to the poor.